Grief: A Brief History of Research on How Body, Mind, and Brain Adapt - O’Connor, Mary-Frances (Psychosom Med, 2019)
OBJECTIVE: Using an integrative view of psychology, neuroscience, immunology and psychophysiology, the present review of literature curates the findings that have had an impact on the field of bereavement research, and shaped its development. METHODS: Beginning with Lindemann’s systematic descriptions of medical and psychological responses to the death of a loved one, specific studies that investigate medical outcomes following loss, their psychological predictors, and biopsychosocial mechanisms are discussed. This selective review culminates in recommendations for the field for future research, including greater integration of these disparate fields of inquiry. RESULTS: Morbidity and mortality following the death of a loved one has long been a topic of research. Early researchers characterized somatic and psychological symptoms and studied immune cell changes in bereaved samples. More recent research has repeatedly demonstrated increased rates of morbidity and mortality in bereaved samples, as compared to married controls, in large epidemiological studies. Recent developments also include the development of criteria for prolonged grief disorder (also termed complicated grief). Newer methods, including neuroimaging, have observed that the greatest impact of the death of a loved one is in those who have the most severe psychological grief reactions. Mechanisms tying bereavement to medical outcomes are scarce, but differences in rumination, in inflammation and in cortisol dysregulation between those who adapt well and those who do not, have been offered with some evidence. CONCLUSIONS: Recommendations to propel the field forward include longitudinal studies to understand differences between acute reactions and later adaptation, comparing samples with grief disorders from those with more typical responses, and integrating responses in brain, mind and body.